Exploring Opportunities for Integrating Building Information Modeling with Circular Economy Principles in Construction: A Survey using Relative Importance Index - Jumadi, Jiescodala; Negara, Kartika Puspa; Wijatmiko, Indradi (Rekayasa Sipil, 2026)
The construction sector in Indonesia—especially in East Java—is expanding rapidly, yet this growth has intensified concerns about resource use, construction waste, and environmental impacts. In this context, adopting Circular Economy (CE) strategies, particularly the 3R principles (reduce–reuse–recycle), has become increasingly urgent. However, practitioners still lack clear, empirically grounded guidance on which Building Information Modeling (BIM)-enabled CE integration opportunities to prioritize for practical implementation in real project environments. To address this gap, this study conducted a purposive-sampling questionnaire survey of BIM-experienced professionals from construction companies with project experience in East Java and prioritized integration opportunities using the Relative Importance Index (RII), preceded by instrument validity and reliability testing. The results indicate that the instrument is statistically robust: all items are valid and demonstrate strong item–total relationships, with excellent internal consistency across the scale. The prioritization shows consistently high agreement across all proposed opportunities. Integrating BIM with green building certifications and standards emerges as the top priority, followed by BIM-based web tools that function as material and component banks to support traceability and circular use. Digital Twin integration and BIM-based decision-support systems form the next priority tier. At the same time, Visual Programming Language (VPL) automation and BIM–Life Cycle Assessment (LCA) implementation remain well perceived but are considered comparatively less urgent. Overall, this research provides a context-specific, evidence-based priority order of BIM–CE integration opportunities for East Java, offering actionable guidance for practitioners and supporting future BIM–CE implementation research in Indonesia.